Association of apolipoprotein E and GLN192ARG paraoxonase 1 gene polymorphisms with hypertension - Ibrahim, Wisam Nabeel; Cho, Maung Maung; Abdullah, Nor Zamzila; Ku Zaifah, Norsidah; Mokhtar, Rafidah Hanim; Draman, Samsul; Md Aris, Mohd Aznan; AR, Rashidah; Aung, Nilar; A.Talib, Norlelawati (2011)
Essential hypertension is a common multifactorial disease which affects 10% to 40% of the population, causing significant cardiovascular morbidity and mortality (P.Trenk et al., 1999). It is believed that hypertension occurs from complex interactions between multiple environmental and genetic factors. Between 30 and 60% of blood pressure variations are determined by genetic factors (Ditto et al., 1993). The molecular mechanisms underlying hypertension are still poorly understood. There are number of genes that have been implicated with hypertension (Richard et al., 2001). ApoE and PON1 genes have been strongly linked with the formation of arthrosclerosis. There were many studies investigating the role of the polymorphisms within these genes with various pathologies including dementia and infectious diseases (M tomása et al., 2004). Apolipoprotein E (Apo E) is a plasma protein responsible for plasma clearance of triglyceride and cholesterol-rich lipoproteins (Mahley et al., 2000) . The ε2, ε3 and ε4 are the three common alleles of this gene. Paraoxonase-1 (PON1) is an esterase enzyme that inhibit LDL oxidation thus altered the development of atherosclerosis (Marta et al., 2004). One of the most important polymorphism within this gene is the codon 192. The correlation of these genes with hypertension were controversial and very few studies tried to illuminate such an issue.